2018
DOI: 10.1002/pros.23478
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA181c inhibits prostate cancer cell growth and invasion by targeting multiple ERK signaling pathway components

Abstract: Downregulation of miR181c results in deregulated ERK signaling and promotes prostate cancer cell growth and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…(33)(34)(35) Multiple molecules act as targets for miR-181c, including Six2 in metanephric mesenchymal cells, FoxO1 in diabetic endothelial cells, transforming growth factor β in glioblastoma cells, PRKCD in ovarian cells, and Erk in prostate cancer cells. (35)(36)(37)(38)(39) Here, we focused on the functional importance of miR-181c down-regulation in HCV-infected hepatocytes. We have observed that HCV-associated down-regulation of miR-181c targets the 3′-UTR, leading to enhanced ATM expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(33)(34)(35) Multiple molecules act as targets for miR-181c, including Six2 in metanephric mesenchymal cells, FoxO1 in diabetic endothelial cells, transforming growth factor β in glioblastoma cells, PRKCD in ovarian cells, and Erk in prostate cancer cells. (35)(36)(37)(38)(39) Here, we focused on the functional importance of miR-181c down-regulation in HCV-infected hepatocytes. We have observed that HCV-associated down-regulation of miR-181c targets the 3′-UTR, leading to enhanced ATM expression.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of miR‐181c may be a prognostic indicator in rapidly proliferating cells, like glioblastoma, osteosarcoma, and ovarian carcinoma . Multiple molecules act as targets for miR‐181c, including Six2 in metanephric mesenchymal cells, FoxO1 in diabetic endothelial cells, transforming growth factor β in glioblastoma cells, PRKCD in ovarian cells, and Erk in prostate cancer cells . Here, we focused on the functional importance of miR‐181c down‐regulation in HCV‐infected hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is closely related to tumor formation. Increased expression of ERK has been detected in a variety of human tumors, especially in GC. It has been shown that the activation of ERK signaling promotes GC growth and metastasis, so it is the most important pathway in the development of GC .…”
Section: Resultsmentioning
confidence: 99%
“…Jung et al13 reported that NFE2L2/NRF2 activity was linked to mitochondria and AMP-activated protein kinase signaling in cancers via miR-181c/mitochondria-encoded cytochrome c oxidase regulation. Su et al14 reported that miR-181c inhibited the growth and invasion of prostate cancer cells by targeting multiple ERK signaling pathway components. Yao et al15 reported that miR-181c inhibited ovarian cancer metastasis and progression by targeting PRKCD expression.…”
Section: Discussionmentioning
confidence: 99%